Analisis Indeks Tingkat Kepuasan Masyarakat Terhadap Pembangunan Infrastruktur di Desa Leppangeng Kecamatan Pitu Riase Kabupaten Sidenreng Rappang - Adnan, Adnan; Sulfanita, Andi; Bustan Didi, Andi (Universitas Sulawesi Tenggara, 2025)
Infrastructure is an economic cog, an important input for production activities and can affect economic activities in various ways both directly and indirectly. To find out how the level of community satisfaction with infrastructure development in Leppangeng Village, Pitu Riase District, Sidenreng Rappang Regency. The purpose of this study was to determine how the level of community satisfaction and what factors influence the level of community satisfaction with infrastructure development in Leppangeng Village, Pitu Riase District, Sidenreng Rappang Regency. The research method used is a questionnaire (questionnaire) conducted in Leppangeng Village, Pitu Riase District, Sidenreng Rappang Regency. The results of the research on the level of community participation related to infrastructure development in general with a satisfied category as many as 69 respondents with a percentage of 84.1% while those who were not satisfied were 13 respondents with a percentage of 15.9% Infrastructure development in Leppangeng Village, Pitu Riase District, Sidenreng Rappang Regency is generally better. And the level of community satisfaction related to infrastructure development in Leppangeng Village is seen based on 8 indicators, namely: Community responses related to procedures 87.8%, community responses related to requirements 90.2%, community responses related to clarity of officers 84.1%, community responses related to officer discipline 89%, community responses related to responsibility 92.7%, community responses related to officer abilities 89%, community responses related to speed 92.7%, and community responses related to justice in infrastructure development in Leppangeng Village are in the satisfied category with a percentage of 90.2%.